Reunderstanding Pemahaman Dasar Teologis Sikap Kekerasan Dalam Rumah Tangga (Telaah Isu Feminisme Hadits Laknat Allah Terhadap Istri) - Fuad Muhammad Zein; Ghulam Falach (Institut Agama Islam Negeri (IAIN) Kediri, 2019)
The problem of gender equality in Islam often uses theological grounds to include the hadith proposition as a tool of legitimacy. Especially in the case of the household, the argument of curse in the relationship of husband and wife is used as the basis for accusations of obtaining domestic violence by the husband to the wife. As if Islam would allow a husband to wife’s violence if they were not willing to serve their sexual desires. This paper aims to answer these assumptions by analyzing the argument of the curse by using the method of critical criticism from the perspective of language or can also be called the bayani method, namely the method of analyzing the meaning of meaning in the argument of fiqh law. The result is that there is an error in understanding the meaning of the hadith caused by a weakness in understanding the meaning in Arabic which is the language of the hadith. Therefore, finally bring conclusions that are less proportional in understanding the propositions and facts. The hadith is a guide for all Muslims and there is no need for doubt in the study of hadith. The development of the modern era certainly has its own influence, especially in the scientific field of hadith. As Muslims of course we are all required to be able to fight in all fields, especially in the field of hadith science. The theoretical uptake and applied form of the Fatima Mernissi methodology of thought have created an important issue to study. His action in terms of knowledge has given rise to new problems for the hadith scientists in the field of feminism. This research aims to examine how the forms of hadiths are based on Fatima Mernissi’s ideas and thoughts. The problem of misogynist traditions is a form of contemporary research that must be discussed, especially regarding the reconstruction of understanding of misogynistic traditions. Few things are important in the study of misogynistic traditions, where the existence of this hadith has created problems for making new facts in the world of feminism. The new fact is nothing but the formation of new weapons in terminating the acceptance or rejection of the hadith. Furthermore, the discussion of this research will be accompanied by the tarjih method in order to arrive at the correct conclusions. Whether the misogynistic hadiths are hadiths that show that Islam discriminates against women or not. The purpose of this study is none other than a study for proving that misogynistic hadiths are not an expression of the hadith denied by Fatima Mernissi to the Muslims’ grip which is expressed in the Qur’an and al-Hadith.